(3fXe GdOQQ GdSfjI aj GdSjQ GdRcjIs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s
(3BNQgG (B:s
(3cedJ HMeO Gdg JYGdi hMSf Yhfg , hUdi Gddg Ydi SjOfG eMeO fHjg hYHOg ai BNQ QLH SfI (B1186(3g` s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B204s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B66 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B70 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B455 s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs